2021
DOI: 10.1111/manc.12361
|View full text |Cite
|
Sign up to set email alerts
|

The causal linkage between inflation and inflation uncertainty under structural breaks: Evidence from Turkey

Abstract: The goal of this paper is to examine the relationship between inflation and inflation uncertainty for Turkey through monthly data spanning the period 2004:01-2019:12. To this 1 See Kara ( 2006) for the details of the implicit inflation targeting strategy in Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Overall, these findings are in line with the recent work of Apergis et al (2021), who, considering Turkey, found that there is no causality between inflation and inflation uncertainty when the main objective of the CBRT was to achieve price stability, whereas when the CBRT tried to achieve both price stability and financial stability (and when the inflation was more heightened and volatile), the Friedman–Ball hypothesis held and rises in inflation led to increased inflation uncertainty.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Overall, these findings are in line with the recent work of Apergis et al (2021), who, considering Turkey, found that there is no causality between inflation and inflation uncertainty when the main objective of the CBRT was to achieve price stability, whereas when the CBRT tried to achieve both price stability and financial stability (and when the inflation was more heightened and volatile), the Friedman–Ball hypothesis held and rises in inflation led to increased inflation uncertainty.…”
Section: Resultssupporting
confidence: 90%
“…To form a more comprehensive measure of uncertainty, Engle (1982), along with Bollerslev (1986), introduced a model recognised as the generalised autoregressive conditional heteroskedasticity (GARCH) model where the conditional variance of a one‐step‐ahead forecast error is utilised as a proxy of inflation uncertainty, and these GARCH models allow for deviations in the conditional variance to persist over time (Ajevskis, 2007). The use of GARCH modelling techniques became prevalent in the literature in testing the inflation–inflation uncertainty link (see Alimi, 2017; Apergis et al, 2021; Jiranyakul, 2020; Tas, 2012, among others), with studies employing different classes of GARCH models, including symmetric and asymmetric models—such as the exponential GARCH (EGARCH) introduced by Nelson (1991); the threshold GARCH (TGARCH) introduced by Zakoian (1994); the Asymmetric Power ARCH (APARCH) model of Ding et al (1993); and the Glosten, Jagannathan and Runkle GARCH (GJR‐GARCH) model—among others.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation